De novo synthesis of 1-phenethylisoquinoline in engineered Escherichia coli - Yaping Mao; Jiangming Zhu; Qian Zhang; Guangyi Wang; Hongkai Fan; Xiaowei Zhang; Yuwei Sun; Yong Wang (Synthetic and Systems Biotechnology)
Phenylethylisoquinoline alkaloids (PIAs) are medicinally important natural products derived from the 1-phenylethylisoquinoline precursor. Heterologous production of the PIAs remains challenging due to the incomplete elucidation of biosynthetic pathway and the lack of proper microbial cell factory designed for precursor enhancement. In this work, an artificial pathway composed of eight enzymes from different species was established for de novo 1-phenylethylisoquinoline biosynthesis in engineered Escherichia coli. The yield of the intermediate 4-hydroxydihydrocinnamaldehyde was optimized through screening various NADP+-dependent 2-alkenal reductases, cofactor regeneration and the site-directed mutagenesis of key residues in ChAER1. Subsequently, incorporation of the modified dopamine pathway into an endogenous reductase-deficient E. coli with high tyrosine yield boosted the production of 1-phenylethylisoquinoline, reaching 402.58 mg/L in a 5L fermenter. Our work lays a foundation for the future large-scale production of high value-added 1-phenylethylisoquinoline-related alkaloids.